Cytomegalovirus contributes partly to uraemia‐associated premature immunological ageing of the T cell compartment. (24th October 2013) - Meijers, R. W. J.; Litjens, N. H. R.; de Wit, E. A.; Langerak, A. W.; van der Spek, A.; Baan, C. C.; Weimar, W.; Betjes, M. G. H.
Summary: Cytomegalovirus (CMV) infection has been implicated in accelerated T cell ageing. End‐stage renal disease (ESRD) patients have a severely immunologically aged T cell compartment but also a high prevalence of CMV infection. We investigated whether CMV infection contributes to T cell ageing in ESRD patients. We determined the thymic output by the T cell receptor excision circle (TREC) content and percentage of CD31+ naïve T cells. The proliferative history of the T cell compartment by determination of the relative telomere length (RTL) and the T cell differentiation status was determined by immunophenotyping. It appeared that CMV infection did not affect thymic output but reduced RTL of CD8+ T cells in ESRD patients. Moreover, increased T cell differentiation was observed with higher percentages of CD57+ and CD28null CD4+ and CD8+ memory T cells. These CD28null T cells had significantly shorter telomeres compared to CD28+ T cells. Therefore we concluded that CMV infection does not affect the decreased thymic output but increases T cell differentiation as observed in ESRD‐related premature T cell ageing.